The Role of Pesantren in Implementing the Educational Triumvirate Through Transformative Heritage in Society 5.0 - Izzat Amini; Abdullah Muhammadi; Nafilatur Rohmah; Wildana Zulfa (Maharot : Journal of Islamic Education, 2025)
Pesantren in Indonesia are currently facing a paradoxical challenge between preserving their traditional values and adapting to the demands of modernization in the era of Society 5.0. This study aims to analyze two main aspects: (1) the role of pesantren in strengthening the synergy of the educational triumvirate, and (2) the concept of Educational Heritage Transformative as a response to the challenges of Society 5.0. This research employs a qualitative approach using a case study design. Data were collected through in-depth interviews with key informants, observations of educational activities, documentation of institutional policies, and Focus Group Discussions (FGDs). Data validity was ensured through credibility, transferability, dependability, and confirmability techniques, while data analysis was conducted through data condensation, data display, and conclusion drawing. The findings indicate that Puncak Darus Salam has successfully implemented the synergy of the educational triumvirate through concrete programs such as the International Class Program (ICP), supported by government collaboration, and the deployment of Guru Tugas (teaching delegates) to various regions, including international contexts. This synergy functions as a collaborative model among Pesantren, government, and society in fostering value-based education and 21st-century competencies. Furthermore, the study proposes the concept of Educational Heritage Transformative as a strategic framework for preserving the distinctive identity of pesantren while simultaneously responding to the challenges of global modernization.